2013
DOI: 10.1142/s146433321350018x
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years of Environmental Impact Assessment System in Bangladesh: Current Practice, Challenges and Future Directions

Abstract: The aim of this article is to review the current practice of EIA system in Bangladesh. In Bangladesh, EIA has been practiced for more than fifteen years. However, there is a lack of scientific information about the current practice of EIA in Bangladesh. This article focused and reviewed three key areas of EIA system in Bangladesh: institutional arrangement, quality of EISs and implementation of mitigation measures. By using a set of good practice criteria, this article finds that still there are shortcomings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…[12]. Environmental impact assessment (EIA) has a play a vital role in achieving these goals [1], [9], [10], and [11]. However, EIA has some limitations but it is important for the country to improve on these limitations with an aim to building a robust of EIA system for sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. Environmental impact assessment (EIA) has a play a vital role in achieving these goals [1], [9], [10], and [11]. However, EIA has some limitations but it is important for the country to improve on these limitations with an aim to building a robust of EIA system for sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…We define capacity as the ability of the EIA organizations to achieve their interests and objectives. In this paper, we focus on the organizational level because the capacities of the EIA organizations largely determine the performance of the EIA system that we would like to improve (Marara et al, 2011;Kabir and Momtaz, 2013;Kolhoff et al, 2016).…”
Section: The Conceptmentioning
confidence: 99%
“…It was at that conference that the role of EIA as an important policy tool for environmental management was first acknowledged by high, middle, and low income countries. However, various studies have shown that in the majority of LMCs, EIA system procedural and substantive performance are both considered to be weak (Annandale, 2001;Wood, 2003;Khadka and Shrestha, 2011;Marara et al, 2011;Kabir and Momtaz, 2013;Kakonge, 2013;Kolhoff et al, 2016;Wells-Dang et al, 2016). Procedural performance is defined as the extent to which the EIA process complies with the EIA legislation (Sadler, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EIA legislation that is unclear, given the capacities and the political context (Bitondo, 2000;Marara et al 2011;Kabir and Momtaz 2013;Kolhoff et al 2009Kolhoff et al , 2013). (Wood 2003;Van Loon et al 2010;Clausen et al 2011;Marara et al 2011;Kabir and Momtaz 2013), including weak monitoring and enforcement capacities (Khadka and Shrestha 2011). 3. Contextual factors such as the political system, the socio-economic situation, and the legal framework (Kakonge 2006;Kolhoff et al 2009Kolhoff et al , 2013Marara et al 2011;Kabir and Momtaz 2013;Wells-Dang et al 2016).…”
Section: Introductionmentioning
confidence: 99%